Young women and desistance: finding a net to fall back on - Abrams, Laura S. (The Palgrave international handbook of youth imprisonment, 2021)
In this chapter, we explore how Black and Latina young women navigate reentry from the juvenile justice system, desistance, and becoming an adult in urban Los Angeles, USA. Much of the literature on youth reentry centers on young men, and less is known about young women. Using longitudinal qualitative interviews with seven young women, we highlight case studies that illustrate how the participants balance individual survival and social supports. Woven throughout, the women’s stories are interconnected through the themes of finding home, breaking the cycle, caregiving, social bonds, gendered violence, and survival and resilience.